Pengaruh Kualitas Produk Dan Citra Merek Terhadap Keputusan Pembelian Konsumen Pada Toko Dian Elektronik Di Kabupaten Luwu Utara - Rahma Isnaini; Moh. Aris Pasigai; Irwan Abdullah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
. This study aims to analyze the effect of product quality and brand image on consumer purchasing decisions at Dian Elektronik Store in North Luwu Regency. This research uses a quantitative approach with multiple linear regression analysis to examine the influence of independent variables on the dependent variable. The sample consisted of 130 respondents who had made purchases at Dian Elektronik Store. The sample size was determined using the Malhotra formula. The collected data were analyzed using SPSS version 25. The results indicate that product quality and brand image have a positive and significant effect on purchasing decisions, both partially and simultaneously. This means that the better the product quality offered and the stronger the brand image, the higher the consumer purchasing decisions at Dian Elektronik Store in North Luwu Regency. Keywords : Product Quality, Brand Image and Purchasing Decision